Experimental evaluation of quasi-static and dynamic compressive properties of ambient-cured high-strength plain and fiber reinforced geopolymer composites - Khan, M.; Hao, Y.; Hao, Hong; Shaikh, Faiz (Elsevier BV, 2018)
Heat cured geopolymer binders have been studied extensively to establish their mechanical behaviour under quasi-static loading conditions and it has been found that they are capable of achieving comparable and in some cases better properties than ordinary Portland cement (OPC). However, as a novel binding material, minimal research has been conducted to understand their dynamic material response. This paper presents the dynamic compressive properties of a newly synthesized high-strength ambient cured geopolymer mortar and hybrid steel-polyethylene fiber reinforced geopolymer composite (FRGC). Dynamic compressive tests are carried out using the Ø100-mm split Hopkinson pressure bar (SHPB) apparatus with pulse shaping technique whereas a 160-ton hydraulic test machine is used for quasi-static compressive tests. The dynamic compressive properties of plain and FRGC including stress–strain curves, strength enhancement, impact toughness and energy absorption capability are obtained and compared with those observed under quasi-static actions. A high-speed camera is used to record the failure processes of samples under impact. The test results show that the dynamic compressive mechanical properties of plain and FRGC exhibit strong strain rate dependency. The DIFs (dynamic increase factors) of samples increase approximately linearly with the average strain rate in a logarithmic manner. Obvious binomial relationships are noticed between the energy absorption capacity and average strain rate of tested samples, such that the strain rate sensitivity threshold exists at 30 s −1 and 66 s −1 for plain and FRGC materials, respectively. Empirical DIF relations are proposed which can be used to model the developed composite materials and structures subjected to static and impact loads.